Field Massage Improves The Life Quality Of Infant With Hyperbilirubinemia And Under Phototherapy - Selia Apriyani; Mariyam Mariyam; Dera Alfiyanti; Amin Samiasih (Universitas Muhammadiyah Semarang, 2021)
Life Quality of an infant is a multidimensional concept that involves physical, emotional, mental, social and other behavioural elements and their function, One of the efforts to maintain the quality of the infant is by field massage. Baby massage is one of the stimulus touches which is also a safe and comfortable form of communication with an infant. The objective of this research to analyze the influence of field massage on the life quality of infants with hyperbilirubinemia and under phototherapy. This research was a quasi-experimental research with one group pre-test-posttest design. with 35 respondents taken as the sample. The data was collected through direct observation on infants life quality before and after the field massage treatment with the assistant of the observation sheet. Life Quality observed include body weight, temperature, pulse, sleep duration, crying time, nighttime awakening intensity. This field massage is done 2x / day (morning and night) within 10 minutes for 2 days in certain areas namely the face chest, stomach, back. The results showed the average infant weight before the massage was 3056.74 after the massage field 3097.14, the baby's temperature before field massage was 36,640 after field massage 36,974, for infant pulse before field massage the average was 142.57 after field massage 141.66, the length of the infant sleep/day before average field massage 14.252 after field massage 16.765, the average intensity of getting up at night/day before the massage field 4.14 after massage field 3.0, the average length of crying of infant/day before the massage field 2,085 after the massage field 1,464. The results of the research showed that the Wilcoxon match pair test for the life quality of infant variable obtained p-value = 0,000 (α = 0.05) meaning that there was a significant effect of field massage on the life quality of infant with hyperbilirubinemia under phototherapy.